Effect of adding different additives on silage quality and milk production of lactating crossbred cows (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The objective of this study was to determine the effect of urea-molasses and di-calcium phosphate additives on silage quality and milk yield of cows. Hence, three types of silages were prepared from Napier fodder namely-Napier silage, urea and molasses added Napier silage (UMN); and di-calcium phosphate added Napier (DCPN) silage. These types of silage fed to the selected nine lactating Holstein-Friesian crossbred cows and divided into three groups considering three of each. Along with 5 kg of respective silages, ad-libitum rice straw and 3 kg concentrate mixture supplied to each group of cows. Physical attributes of all prepared silages were possessing characteristics of good quality silage. Dry matter content in UMN and DCPN silages were 1.67 and 1.01% higher than Napier silage. UMN silage had 1.59 and 2.33% lower ADF from Napier and DCPN silage, respectively. Again, 1.29% higher NH3-N presents in UMN silage than Napier silage. From 1st to 4th fortnight milk yield data it was found that 23.70, 23.19 and 27.06% milk production increased those cows received Napier, UMN and DCPN silage, respectively. Considering above these, it might be concluded that addition of di-calcium phosphate as additive during silage making would be beneficial for the dairy farmers.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 40-44